A efetivação da liberdade no estado hegeliano - Souza, Bárbara Santiago de (2015)
This research intends to clarify the relationship between freedom and State in Hegel’s philosophy. In order to do that, a directional reading of “Philosophy of Right” will allow to identify the importance of the hegelian thought, to perform a reflection about the issue between the individual’s freedom and the State’s paper in the effectiveness of this freedom. Hegel says that the State produces the ideal conditions for the development of individual’s rights. However, this subjective freedom keeps being inappropriate and incapable of produce its stability and sustentability. Thereby, it’s necessary, in the other hand, that the State takes de function of ensure this stability. The State takes this function because it is organic and selfsufficient, and this as far as represents the objective dimension of freedom. Finally, the substancial freedom became possible to the reflective individuals inside the State. So, to get access to this final freedom, the individual must take actively part of the State through the institutions that offer the possibility of living an ethic life, that means living the reconciliation between individual and State, and so it became possible the effectiveness of this individual freedom.